Application of Modified Kite Flap in Reconstruction of Facial Wounds After Operation and Case Series - He G; Yang Q; Shen Y; Zhang L; Wu J; Cheng H (Dove Medical Press, 2024)
Guanjin He,1,* Qifeng Yang,2,* Yuyang Shen,3 Lanzhi Zhang,2 Jingping Wu,2 Hongbin Cheng1 1Dermatology Department, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, People's Republic of China; 2Medical Aesthetic Department, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, People's Republic of China; 3Traditional Chinese Medicine Department, The Third People's Hospital of Chengdu, Chengdu, People's Republic of China*These authors contributed equally to this workCorrespondence: Jingping Wu; Hongbin Cheng, Hospital of Chengdu University of Traditional Chinese Medicine, No. 39, Shi-Er-Qiao Road, Jinniu District, Chengdu, People's Republic of China, Tel +86 15928747715 ; +86 13880848134, Email jingpingwu2022@163.com; chenghongbin@cdutcm.edu.cnAbstract: Our team used a new kite flap preparation method to repair wounds after the removal of a benign facial tumor with satisfactory aesthetic results. Thus, this modified kite flap has significant value in facial trauma repair.Keywords: facial wound repair, modified kite flap, experience, case series